GAMBARAN PEMULIHAN KEPERCAYAAN INDIVIDU DEWASA AWAL YANG MENGALAMI PERSELINGKUHAN DALAM HUBUNGAN ROMANTIS - Marfine; Riana Sahrani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Infidelity in romantic relationships often causes significant damage to trust between partners. Restoring broken trust requires substantial effort, a process known as trust repair. This study aims to explore the trust repair process in early adulthood individuals who have experienced infidelity in romantic relationships. Using a qualitative approach, in-depth interviews were conducted with five participants who experienced infidelity. The findings show that trust repair involves several stages, including acknowledgment of mistakes, apology, compensation, and forgiveness. Key factors supporting the success of trust repair include honest communication, consistent behavioral change, and commitment to restoring the relationship. This study contributes to a deeper understanding of how to repair trust broken by infidelity in romantic relationships.